Study of reduce, reuse and recycle techniques in sustainable construction waste management - Fatimah Hanim, Khairudin (2015)
Construction industry consume substantial amount of raw materials in the process and the output is the product with the waste production. Other than that, construction industry is major environment polluters. This study is to determine the use of waste minimization technique in creating sustainable waste management in order to identify the technique which has the most capabilities to reduce waste on-site. The objective of the study is to assess the techniques from 3R concept which is reduce, reuse and recycle in minimizing the waste in construction waste management. Questionnaires have been distributed randomly across the district of Kuala Lumpur and the data has been analysed. The most used technique would be the waste reduction. This proves that local construction industry has the awareness to plan out the waste management planning but the implementation in the communities is still far from satisfying. This has been shown with the results of the second objective which shows that none of the techniques in the 3R gave a significant relationship in minimizing the waste produce in site. However, among the three techniques, the recycle technique did give a significant difference. This proves that profits gave more reasoning for the construction practitioners to adapt to this technique because the nature of the industry which is profit making